The effects of ceramic fillers on the PMMA-based polymer electrolyte systems - Tan, C. G.; Siew, W. O.; Pang, W. L.; Osman, Z.; Chew, K. W. (SPRINGER HEIDELBERG, 2007)
The effects of ceramics fillers on the polymethylmethacrylate (PMMA)-based solid polymer electrolytes have been studied using ac impedance spectroscopy and infrared spectroscopy. The polymer film samples were prepared using solution cast technique, tetrahydrofuran (THF) used as a solvent, and ethylene carbonate (EC) has been used as plasticizer. Lithium triflate salt (LiCF3SO3) has been incorporated into the polymer electrolyte systems. Two types of ceramic fillers, i.e., SiO2 and Al2O3, were then implemented into the polymer electrolyte systems. The solutions were stirred for several hours before it is poured into petri dishes for drying under ambient air. After the film has formed, it was transferred into desiccator for further drying before the test. From the observation done by impedance spectroscopy, the room temperature conductivity for the highest conducting film from the (PMMA-EC-LiCF3SO3) system is 1.36x 10(-5) S cm(-1). On addition of the SiO2 filler and Al2O3 filler, the conductivity are expected to increase in the order of similar to, 10(-4) S cm(-1). Infrared spectroscopy indicates complexation between the polymer and the plasticizer, the polymer and the salts, the plasticizer and the salts, and the polymer and the fillers. The interactions have been observed in the C=O band, C-O-C band, and the O-CH3 band.